การประยุกต์ใช้โปรแกรม มอนติ คาร์โล เอ็น พาร์ติเคิล เพื่อพัฒนาวิธีการคำนวณปริมาณรังสีดูดกลืนในอวัยวะบริเวณ ช่องเชิงกรานจากการตรวจด้วยเอกซเรย์คอมพิวเตอร์ - เจนจิรารักษ์ ฤทธิ์ปัญจะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Computed Tomography (CT) is a medical imaging procedure which produces a number of cross-sectional images of a scanned patient for diagnostic purposes. Taking many X-ray exposure from different angles to obtain those images, the procedure inevitably imposes on the patient higher dose than conventional radio-imaging procedures. This study is therefore aimed to determine absorbed dose in pelvic organs using a computer code, A General Monte Carlo N-Particle Transport Code version 5 (MCNP5). The MCNP5 simulation model is successfully validated by comparing a set of absorbed doses calculated from MCNP5 and a set of direct measurements based on 19 OSL nanodot dosimeters in RANDO phantom. The validated MCNP5 models used to determine absorbed doses of urinary bladder, uterus, prostate gland and ovaries of 4 individual patients (male1, male2, female1 and female2). The results show that eleven absorbed doses of internal organs from MCNP5 and OSL dosimeters are in good agreements as their differences are less than 10 percent. However, eight absorbed doses from skin area are observed to have their differences higher than 10 percent. When using MCNP5 to evaluate absorbed dose in pelvic organs from CT procedure, it shows that the maximum doses are 28.27 cGy and 37.79 cGy at urinary bladders for male1 and male2, respectively. In case of two female patients, the maximum absorbed doses are 76.89 cGy and 77.96 cGy at uterus for female1 and female2, respectively which are inversely proportionally to an effective diameter of a patient. The correlation test of absorbed dose between MCNP5 calculation and dose length product (DLP) exhibits a very weak correlation with Pearson product-moment correlation coefficient (r) equal to 0.031 (p-value 0.05). It is concluded that MCNP5 is an effective tool to evaluate absorbed doses in important organs from CT procedure and subsequently contributes to the assessment of the radiation risk for patients.